Infancia y transgresión poética en la obra de Luis Hernández - León Mango, Liz Fiorella (2021)
In the ideology of the modern poet, childhood represented the lust for knowledge, the playful-experimental impulse and the material conscience of art. These features can be distinguished in the work of Luis Hernandez, who, revaluing childhood, set out the playful impulse and innocence as keys to an original artistic production. Identifying himself with the purity of a child, on a thematic level, the poet questioned the indolence and the organizational and alienating eagerness of all authoritarianism. As for the use of technical-formal instruments, he practiced with them just like a child experiments with his play objects, exploiting his possibilities, carefree and irreverent. That said, our objective is to show how his reinterpretation of childhood influenced his questioning of the processes of writing, distribution and reception of literature.